2014
DOI: 10.1287/moor.2013.0637
|View full text |Cite
|
Sign up to set email alerts
|

Probability Bounds for Polynomial Functions in Random Variables

Abstract: Random sampling is a simple but powerful method in statistics and the design of randomized algorithms. In a typical application, random sampling can be applied to estimate an extreme value, say maximum, of a function f over a set S ⊆ R n . To do so, one may select a simpler (even finite) subset S 0 ⊆ S, randomly take some samples over S 0 for a number of times, and pick the best sample. The hope is to find a good approximate solution with reasonable chance. This paper sets out to present a number of scenarios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 24 publications
0
33
0
Order By: Relevance
“…uniform distribution on Ω m . As each component of x ξ defined by (8) belongs to conv (Ω m ), by Lemma 5.2, there exists y ∈ Ω n m such that…”
Section: Conjugate Form In the M-th Roots Of Unitymentioning
confidence: 98%
See 2 more Smart Citations
“…uniform distribution on Ω m . As each component of x ξ defined by (8) belongs to conv (Ω m ), by Lemma 5.2, there exists y ∈ Ω n m such that…”
Section: Conjugate Form In the M-th Roots Of Unitymentioning
confidence: 98%
“…So [23] further considered spherically constrained homogeneous polynomial optimization and proposed a deterministic algorithm with an improved approximation ratio. For most recent development on approximation algorithms for homogeneous polynomial optimization, we refer the interested readers to [8,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Constructx = ξ/ ξ 2 , then we have Prob(f (x) 3 2/θf min (HQQS)) θ/2 with θ := 1/960. As far as we know, the best approximation ratio for quartic polynomial optimization with a single sphere constraint is O(n/ ln n) in [12,25], and the ratio under consideration is relative ratio. The merit of our approximation scheme is that both approximation ratios obtained by our two algorithms are absolute ones.…”
Section: Theorem 36mentioning
confidence: 99%
“…Since polynomial optimization problems are generally NP-hard, various polynomialtime approximation algorithms have been proposed for solving certain classes of high-degree polynomial optimization models-a summary of research can be found in the monograph of Li et al [21]. Improvements on approximation ratios of these polynomial optimization models have been recently made by He et al [8] and Hou and So [12]. In the context of complex polynomial optimization, approximation algorithms are mostly proposed for the quadratic models.…”
Section: Introductionmentioning
confidence: 99%